Spread of Multidrug-resistant microrganisms: a global threat and critical healthcare problem - Paulo P. Gontijo Filho; Cristiane Silveira Brito; Lícia Ludendorff Queiroz; Daiane Silva Resende; Bruna Fuga Araujo; Rosineide Marques Ribas (Universidade de Santa Cruz do Sul, 2016)
Multidrug-resistant organisms are usually associated with greater number of clinical manifestations and severe infections than those caused by susceptible pathogens. The high prevalence of antimicrobial resistance is a global concern, mainly in Latin America, where resistance levels are higher for important pathogens such as Gram-negative non-fermentative bacteria and Enterobacteriacae family, compared with those seen in US hospitals and Europe. The use of antimicrobial agents for the treatment of these infections is advantageous for the multidrug-resistant pathogens and contributes to the maintenance of the genetic determinants of resistance. Countries like Brazil, characterized by the allocation of limited financial resources for the health department, have in the infection prevention and control practices an economical necessity, because of the increased costs that nosocomial infection demand in addition to the reduction of rates morbidity and mortality.